Characteristics of Water Quality and Sediment Distributions on the Northeastern Coast of Jeju Island - Taehee Lee; Hyung Jeek Kim (Geo Data)
Since the 1980s, the number of land-based fish farms on Jeju Island has increased rapidly. With increasing land-based fish farms, a large amount of nutrients from fish farm wastewater is discharged off the coast of Jeju. To understand the characteristics of coastal seawater and the ecological environment on the coast of Jeju, the effect of land-based fish farm effluent on coastal seawater should be evaluated. Temperature, salinity, nutrients, and chlorophyll-a concentration were investigated on the northeastern coast of Jeju during June and July 2023. Nitrate, phosphate, and silicate concentrations in the surface waters were significantly higher in coastal stations than in the outer stations. Unlike the surface waters, nutrient concentrations in the bottom waters are distinctly higher in land-based fish farm effluent stations than in the outer stations. Total organic carbon content in surface sediment was significantly higher in land-based fish farm effluent stations than in the outer stations. This study may provide valuable information for evaluating the impact of land-based fish farm effluent on coastal ecosystems on Jeju Island.